2011
DOI: 10.1007/s10661-011-2479-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of traditional coffee processing on river water quality in Ethiopia and the urgency of adopting sound environmental practices

Abstract: Although waste from coffee processing is a valuable resource to make biogas, compost, and nutrient-rich animal food, it is usually dumped into nearby water courses. We carried out water quality assessment at 44 sampling sites along 18 rivers that receive untreated waste from 23 coffee pulping and processing plants in Jimma Zone, Ethiopia. Twenty upstream sampling sites free from coffee waste impact served as control, and 24 downstream sampling sites affected by coffee waste were selected for comparison. Physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 12 publications
2
43
1
Order By: Relevance
“…The by-products are known to be rich in organic pollutants (e.g., proteins, sugars, and pectin), tannins, and phenolic compounds harmful to plants, humans, and aquatic biota [9,10]. Globally, coffee processing generates about 15 × 10 6 Mg (dry weight basis) of coffee residues, of which 9.4 × 10 6 Mg is pulp [11].…”
Section: Introductionmentioning
confidence: 99%
“…The by-products are known to be rich in organic pollutants (e.g., proteins, sugars, and pectin), tannins, and phenolic compounds harmful to plants, humans, and aquatic biota [9,10]. Globally, coffee processing generates about 15 × 10 6 Mg (dry weight basis) of coffee residues, of which 9.4 × 10 6 Mg is pulp [11].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported that untreated waste from traditional and modern industries is threatening surface waters worldwide, and it is severe in developing countries (Beyene et al 2011). Water pollution is the gloomy setback for the development in coffee producing countries (Mwaura and Mburu 1998;Varunprasath and Daniel 2010), and this also appears to be the case in Ethiopia (Haddis and Devi 2008;Beyene 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Traditional shedding coffee plantation system, which has social and economic value (Vergara and Badano 2009) with minimal impact on biodiversity and environment (Perfecto et al 1996;Gordon et al 2007;López-Gómez et al 2008), prevails in Jimma Zone. Nevertheless, untreated waste materials from coffee processing are routinely discharged into local streams without treatment and caused a severe ecological disruption (Beyene et al 2011). Coffee processing is vilified for the production of byproducts such as parchment husks, coffee pulp and coffee husks all of which contribute to environmental pollution unless treated or recycled (Mburu and Mwaura 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Currently in vietnam, coffee waste management systems are not well established. Several studies reported that untreated waste from traditional and modern industries is threatening surface waters worldwide, and it is severe in developing countries (6) . Water pollution is the gloomy setback for the development in coffee producing countries (7,8) , and this also appears to be the case in Ethiopia and Vietnam (9)(10)(11) .…”
Section: Envrinmental Effects Of Coffee Processingmentioning
confidence: 99%